Українська історична наука 90-х років ХХ століття: пошук нових методологічних координат - Зякун, А. (Світогляд - Філософія - Релігія, 2011)
Аналізується методологічний плюралізм, що сформувався в українській історичній науці в останнє десятиліття ХХ ст. The process of forming new Ukrainian historian methodological grounds of the national historical science are in three areas: restore the best traditions of national historical school, development new world achievements, working on modern methodological approaches.